THE INFLUENCE OF ZAKAT LITERACY, INCOME AND BELIEFS ON MUZAKKI'S DECISION TO PAY ZAKAT VIA FINTECH PLATFORM IN PADANG LAWAS DISTRICT-NORTH SUMATRA - Romatua Lubis (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2023)
The aim of this research is to find out whether Zakat Literacy, Income and Trust have a partial and simultaneous influence on the muzakki's decision to pay zakat via the Fintech Platform in Padang Lawas Regency. To find out what variables have the most influence on the muzakki's decision to pay zakat via the Fintech Platform in Padang Lawas Regency. and to find out whether the method of paying zakat carried out by the people of Padang Lawas Regency is in accordance with Sharia Economic Principles. The data collection methods used were questionnaires, observation and documentation. Then analyzed using SEM (Structural Equational Model) with Multiple Regression analysis using the Smart PLS (Partial Least Square) application. The research results show that Zakat Literacy, Income and Trust have a partial and simultaneous influence on muzakki's decision to pay zakat via the Fintech Platform in Padang Lawas Regency. Zakat literacy has the most dominant influence on muzakki's decision to pay zakat via the Fintech Platform in Padang Lawas Regency, and zakat payments made by the people of Padang Lawas Regency via the Fintech Platform are in accordance with the teachings and principles of Sharia Economics.